Human Lung Local Immunity to Influenza Virus-Role of Lung Antibody and Resident Memory T Cells - Chan, Renee WY; Valkenburg, Sophie A; Fong, Joanne HM; Cheung, Man Chun; Kuok, Denise IT; Islam, Md A; Peiris, JSM; Nicholls, John M; Poon, LLM; Chan, Michael CW (Archives of Clinical and Biomedical Research, 2024)
Human lung explant cultures have been used extensively to risk assess the replication competence and disease severity when a new respiratory virus emerges. In the 2009 H1N1 pandemic, we observed an interesting pattern of a steep increase in H1N1pdm virus replication in the human lung ex vivo culture collected from April to July 2009 to the almost flattened replication curve in the period of August 2011 to July 2012 onwards. As the lung explant system is isolated from the circulatory immunity, we aimed to determine the effect of the lung local immunity towards the influenza virus by measuring the antibody levels in the lung epithelial lining fluid (ELF) and the involvement of tissue-resident memory T cells. Lung ELF contained IgA and measurable IgG however, it is not sufficient to neutralize the influenza virus used in the current study. CD8+ T resident memory (TRM) cell and the CD4+TRM cell can be found in the lymphocyte population isolated from the lung. Interestingly, TRM CD8+Tet+ was associated with a trend of reduced replication competence of H1N1pdm in the lung explant culture but not in seasonal H1N1. The presence of influenza-strain-specific CD8+TRM might reduce the virus replication competence in the local epithelium.